Utilization of Medicinal Plants by Malay and Javanese Tribes in Bukit Peranginan Village, Mandiangin District, Sarolangun Regency - Titi Muntasaro; Try Susanti; Suraida Suraida; Aini Qomariah Manurung (Jurnal Biologi Tropis, 2023)
This research study how the Malay and Javanese tribes in Bukit Peranginan Village, Mandiangin District, and Sarolangun Regency use medicinal plants. The purpose to identify the various types of medicinal plants, how to use them, and their cultural significance. This study used a qualitative descriptive methodology, and the value of the Cultural of Significance Index (ICS) was derived for the quantitative data analysis. The results showed that there were 25 families and 37 plant species overall, with Zingiberaceae being the largest family. For the Malays and the Javanese, up to 8 species of plants and 21 different types of plants, respectively, have leaves that are frequently used as medicine. Boiling up to 21 different plant species is the primary method of using plants as medication. The importance of preserving the cultural properties of plants used by the Malay and Javanese tribes in Bukit Peranginan Village as traditional medicines, particularly Curcuma longa L, which has values of 171 and is used as a treatment for ulcers, cholesterol, colds, vaginal discharge, diabetes, wound medicine, abdominal pain, and postpartum pain.